Laser-induced periodic surface structures on Fe ion doped LN crystal for pyroelectric SERS analysis - Ren, Yingying; Luo, Shenglin; An, Peng; Zhao, Lina; Cai, Yangjian; Li, Zhen (Applied physics letters, 2024)
We proposed a sensor architecture for surface-enhanced Raman scattering (SERS) based on Fe ion doped LN (FLN) crystal, which was modified by large-area laser-induced periodic surface structures (LIPSS) and subsequently decorated with Ag nanoparticles (Ag NPs). Based on such a FLN/LIPSS/Ag substrate, strikingly boosted SERS enhancement was obtained at constant temperature owing to the LIPSS-related hot spot improvement. Benefiting from the pyroelectric effect of the FLN crystal, further enhanced SERS was achieved under heating and cooling processes, which can be ascribed to the additional charge transfer between molecules and Ag NPs triggered by pyroelectric potential. The experimental results highlight the high fabrication efficiency, ultrasensitivity, high uniformity, and high universality of the substrate, integrating the advantages of both LIPSS and the FLN crystal. More interestingly, selective suppression of Raman signals under cooling processes was observed, which further extends the applications of the FLN/LIPSS/Ag substrate for the detection of molecule complexes such as lake water polluted by crystal violet and 4-aminothiophenol molecules.